2007
DOI: 10.1309/1kb2gkyt1bueylb5
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Growing Mycobacteria

Abstract: We analyzed clinical and microbiologic features of 115 cases involving rapidly growing mycobacteria (RGM) isolated at the University of Texas M.D. Anderson Cancer Center, Houston (2000-2005) and identified by 16S ribosomal RNA gene sequencing analysis. At least 15 RGM species were included: Mycobacterium abscessus (43 strains [37.4%]), Mycobacterium fortuitum complex (33 strains [28.7%]), and Mycobacterium mucogenicum (28 strains [24.3%]) most common, accounting for 90.4%. Most M abscessus (32/43) were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(48 citation statements)
references
References 3 publications
3
45
0
Order By: Relevance
“…M. abscessus was found in 65% of pulmonary RGM disease, and the ratio of patients who met the diagnostic criteria to patients from whom RGM was isolated was highest in those patients with M. abscessus. This result also coincided with the results of previous reports in which M. abscessus was found to be the most virulent pathogen in pulmonary RGM disease [5,8,11,19]. The patients in the present study were lean, aged and did not show any sex bias.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…M. abscessus was found in 65% of pulmonary RGM disease, and the ratio of patients who met the diagnostic criteria to patients from whom RGM was isolated was highest in those patients with M. abscessus. This result also coincided with the results of previous reports in which M. abscessus was found to be the most virulent pathogen in pulmonary RGM disease [5,8,11,19]. The patients in the present study were lean, aged and did not show any sex bias.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 50% of patients with pulmonary RGM disease in the present study had respiratory symptoms and no smoking history. Most of these results are concordant with the results in previous reports [5,8,19]. M. abscessus was found in 65% of pulmonary RGM disease, and the ratio of patients who met the diagnostic criteria to patients from whom RGM was isolated was highest in those patients with M. abscessus.…”
Section: Discussionsupporting
confidence: 91%
“…RGM, though traditionally believed to be non-pathogenic or opportunistic species, have emerged as significant human pathogens, causing various infections in healthy and immunocompromised hosts. 16 This underscores the importance of the accurate interpretation of findings on culture and the use of confirmatory tests. The recognition of RGM has significant implications for treatment purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study on 115 cases infected with Rapidly Growing Mycobacteria showed M. abscessus to be the commonest NTM in 43 out of 113 (38.05%) cases and was most commonly isolated from the respiratory tract, 32/43 cases (74%); other sites being bloodstream, tissues and ascitic fluid, which made up the rest of the samples [11]. Due to intrinsic resistance to all the first line Anti-Tubercular drugs, M. abscessus infection is difficult to treat.…”
Section: Discussionmentioning
confidence: 99%